Tруднощи використання термінів при атрибуції холодної зброї - Літвінов, В.В. (Культура народов Причерноморья, 2013)
В статті проаналізовано труднощі визначення типу та назви холодної зброї українською
мовою. Запропоновано варіант розв’язання цього питання.
Ключові слова: термін, зброя, переклад, митниця. В статье проанализированы трудности определения типа и названия холодного оружия на
украинском языке. Предложен вариант решения этого вопроса.
Ключевые слова: термин, оружие, перевод, таможня. The culture values – the various objects material and spiritual culture, which have archaeology,
anthropology, historical, literature, art and scientific values for national and word cultures. The task for
customs officers in skill identification and make an inventory the culture values. There are multitude kinds the
culture values which it is necessary different forms for their description. The weapon is one of kinds the culture
values. The author propose rule for identification given form the culture values. The sources of building the
visual thumbnails of the culture values in human are analyzed in this work. The author reasons of mistaking
attribution of cultural values.
Key words: weapon, customs.